Temperature Stress Induces Shift From Co-Existence to Competition for Organic Carbon in Microalgae-Bacterial Photobioreactor Community – Enabling Continuous Production of Microalgal Biomass - Sörenson, Eva; Capo, Eric; Farnelid, Hanna; Lindehoff, Elin; Legrand, Catherine (Frontiers in Microbiology, 2021)
To better predict the consequences of environmental change on aquatic microbial ecosystems it is important to understand what enables community resilience. The mechanisms by which a microbial community maintain its overall function, for example the cycling of carbon, when exposed to a stressor, can be explored by considering three concepts: biotic interactions, functional adaptations and community structure. Interactions between species are defined as either coexistence or competition, functions relate to their metabolism and roles in ecosystem functioning (e.g., oxygen production, organic matter degradation), and structure align with species richness and diversity, where a diverse community is though to exhibit a broader functional capacity than a less diverse community. These concepts have here been combined with ecological theories commonly used in resilience studies, i.e. adaptive cycles, panarchy and cross-scale resilience, that describe how the status and behavior at one trophic level impact that of surrounding levels. This allows us to explore the resilience of a marine microbial community, cultivated in an outdoor photobioreactor. The culture was monitored for 6 weeks during which it was exposed to two different temperature regimes (21±2°C and 11±1°C). Methods include metatranscriptomic analyses, in order to assess the carbon uptake and utilization, and amplicon (18S and 16S rRNA gene) sequencing, to characterize the community structure of both autotrophs and heterotrophs. Differential gene expression analyses suggested that community function at warm temperatures was based on concomitant utilization of inorganic and organic carbon assigned to autotrophs and heterotrophs, while at colder temperatures, the uptake of organic carbon was performed primarily by autotrophs. Going from high to low temperature, community interactions shifted from coexistence to competition for organic carbon. Network analysis indicated that the community structure showed opposite trends for autotrophs and heterotrophs in being either generalist or specialist. Despite an abrupt change of temperature, the microbial community as a whole responded in a way that maintained the overall level of diversity and function within and across autotrophic and heterotrophic levels. This is in line with cross-scale resilience theory describing how ecosystems may balance functional overlaps within and functional redundancy between levels in order to be resilient to environmental change.